Chemistry of ruthenium σ-borane complex, [Cp∗RuCO(μ-H)BH2L] (Cp∗ = η5-C5Me5; L = C7H4NS2) with terminal and internal alkynes: Structural characterization of vinyl hydroborate and vinyl complexes of ruthenium. (29th March 2017) - Saha, Koushik; Joseph, Benson; Borthakur, Rosmita; Ramalakshmi, Rongala; Roisnel, Thierry; Ghosh, Sundargopal
Graphical abstract: Reaction of ruthenium σ-borane complex [Cp ∗ RuCO(μ-H)BH2 L] (Cp ∗ = η 5 -C5 Me5 ; L = C7 H4 NS2 ) with alkynes form ruthenium vinyl hydroborate and vinyl complexes. Abstract: The chemistry of ruthenium–borane complex, [Cp ∗ RuCO(μ-H)BH2 L] (Cp ∗ = η 5 -C5 Me5 ; L = C7 H4 NS2 ), 1 with various alkynes has been explored. Photolysis of1 with alkynyl-Grignard, [HCCMgBr] in toluene led to the isolation of vinyl hydroborate complex [Cp ∗ Ru(μ-H)BHHCCH2 L], 2a as a sole product. Compound2a can be viewed as a ruthenium–borate complex with an ethylene moiety. Further, the chemistry of1 with various internal and terminal alkynes has been performed in photolytic conditions. Photolysis of1 with [RCCR] (R = CO2 Me) yielded vinyl hydroborate complex [Cp ∗ Ru(μ-H)BClRCCRL], 2b . Terminal alkynes [HCCR] (R = Ph or CO2 Me) under the same reaction conditions led to the isolation of metal vinyl complexes [Cp ∗ Ru(CO)(C2 HR)(L)], 3a and3b (3a : R = Ph;3b : R = CO2 Me). In addition, DFT calculations were carried out to analyze the bonding and electronic structures of these new compounds.